Biological variation of major gut‐derived uremic toxins in the serum of healthy adult cats. (3rd February 2021) - Summers, Stacie; Quimby, Jessica; Yao, Linxing; Hess, Ann; Broeckling, Corey; Lappin, Michael
Abstract: Background: Biological variation of serum indoxyl sulfate (IS), p‐cresol sulfate (pCS), and trimethylamine‐n‐oxide (TMAO) concentrations in cats is unknown. Objectives: To determine short‐ and medium‐term biological variation, index of individuality (II), and reference change values for serum IS, pCS, and TMAO concentrations in healthy adult cats. To determine the effect of feeding on serum concentrations. Animals: Twelve healthy adult cats. Methods: Prospective, cohort study. Seven serum samples over a 12‐hour period (short‐term) and 5 serum samples over a 19‐day period (medium‐term) were collected. Serum concentrations of total IS, pCS, and TMAO were measured every 2 hours in a 12‐hour period (hours 0‐12) after a meal in 9 cats and compared to concentrations in a nonfed state. Results: For IS, the II was high using short‐term (1.96) and low using medium‐term (0.65) biological variation estimates. Individuality was intermediate for pCS (short‐term, 0.98; medium‐term, 1.17) and TMAO (short‐term, 1.47; medium‐term, 0.83). Serum IS, pCS, and TMAO concentrations were significantly lower in a fed state compared to a nonfed state at hours 4, 6, 8, and 12; at hours 4 and 6; and at hours 2, 4, 6, 8, 10, 12, respectively. Conclusion and Clinical Importance: Population‐based reference intervals with reference to the subject‐based interval can be used to monitor serum pCS and TMAO concentrations. For IS, a subject‐based and a population‐based reference interval is best for short‐term and medium‐term monitoring, respectively. To compare serial measurements, it would be prudent to collect samples at the same time of day and consistently in either a fed or nonfed state.